Nekatere značilnosti ustroja Maribora - Drozg, Vladimir (Geografski vestnik, 1997)
The paper is an attempt of synthetic presentation of certain elements of urban structure. It is based on the comparison, linking and explanation of the quality of dwelling environment, the degraded areas, and the central areas of Maribor. A structural scheme of Maribor is presented in the conclusion.
Keywords: družbena geografija; human geography; Maribor; mesta; urbana naselja